THE ROLE OF SHARIA BANKING ON MSMEs THAT IMPLIED ON INDONESIAN ECONOMIC GROWTH - Neneng Nurbaeti Amien; Wandy Zulkarnaen (Komitmen: Jurnal Ilmiah Manajemen, 2022)
This is a descriptive qualitative study that employs secondary material acquired from a variety of sources in the form of theories, reports, research findings, and so on. The goal of this study is to examine the influence of Islamic banking in MSMEs in the growth of the Indonesian economy. The years 1997 and 1998 saw terrible economic conditions; nonetheless, only the MSME sector (micro, small, and medium companies) was able to recover and grow after the crisis. The number of micro, small, and medium-sized enterprises (MSMEs) does not drop, but rather increases. One of the key goals of Sharia banking projects in the country's economic development process is the supply of capital through micro, small, and medium firms. Along with the Indonesian government's emphasis on the development of micro, small, and medium-sized firms (MSMEs), the Islamic banking industry helps to the empowerment of these MSMEs, which will eventually progress economic sectors and boost economic growth.